Ceramic substrate, ceramic circuit substrate, semiconductor device, method for manufacturing ceramic substrate, and method for manufacturing ceramic divided substrate
By forming specific energy spectrum peaks on the laser processing surface of the ceramic substrate, the problem of insufficient depth of the scribe line and thermal influence of the ceramic substrate during laser processing is solved, and high-intensity and high-thermal conductivity of small ceramic substrates are achieved efficiently, thereby improving segmentation Quality and cost-effective.
Patent Information
- Application Number
- CN202380041755.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-31
AI Technical Summary
During laser processing, existing ceramic substrates have insufficient scribe depth due to high strength and high toughness, making it difficult to efficiently segment, and the heat influence leads to oxidation of silicon compounds, affecting the quality of segmentation.
By forming peaks above 98 eV and below 106 eV on the laser processing surface of the ceramic substrate, the X-ray photoelectron spectroscopy is used to determine the intensity of the scribe lines, increase the torque, suppress the adverse phenomena during segmentation, and pass the multiple methods of multi-dimensionality Sub-laser irradiation and auxiliary gas are used to reduce heat effects.
It is realized efficiently manufacturing small substrates from large ceramic substrates, which improves cost performance, reduces poor division, and enhances the high strength and high thermal conductivity of ceramic substrates.
Smart Images

Figure CN119234305A_ABST
Abstract
Description
Technical Field
[0001] The embodiments generally relate to a ceramic substrate, a ceramic circuit substrate, a semiconductor device, a method for manufacturing a ceramic substrate, and a method for manufacturing a ceramic divided substrate. Background Art
[0002] In recent years, with the development of semiconductor devices that require large currents, such as power electronics and next-generation power semiconductors, the demand for ceramic substrates that have both heat dissipation and electrical insulation has increased year by year. In particular, as the heat generated by components increases with miniaturization and high performance, the thickness of ceramic substrates tends to become thinner in order to efficiently dissipate heat.
[0003] On the other hand, in order to reduce the manufacturing cost of ceramic substrates, they are manufactured in larger shapes. Among ceramic substrates, silicon nitride substrates having high strength, high toughness and high heat dissipation have been disclosed in a size of 220 mm×220 mm×0.32 mm (Patent Document 1).
[0004] As one of the methods for dividing a silicon nitride substrate as a ceramic substrate that is manufactured in large size to reduce manufacturing costs into product sizes to be used, a method for performing multi-piece processing using scribing lines formed by laser processing is disclosed (Patent Document 2). According to Patent Document 2, when dividing with multi-piece processing by laser processing, microcracks of the silicon nitride substrate that are more than necessary are not generated, and scribing processing for multi-piece processing can be performed easily and at low cost.
[0005] On the other hand, since the substrate before division becomes significantly thinner, the technical problems caused by laser processing of a ceramic substrate with high strength and high toughness are clarified. For example, the ceramic substrate has high strength, so a large force is required to break along the scribe line, so the laser needs to penetrate deeper in the thickness direction of the ceramic substrate. However, in order to form the scribe line deeply in the thickness direction like this, a large amount of energy is required. When the energy of the laser is converted into the energy of the scribe line, a part of it is converted into heat energy. When the conversion ratio to the heat energy is large, the thermal effect becomes larger. Therefore, it is often the case that the oxidation of the silicon compound progresses due to the heat effect.
[0006] In previous laser-processed surfaces, when XPS (X-ray Photoelectron Spectroscopy) was used to measure the processed surface, no more than two peaks above 528eV and below 536eV were observed at any part. Therefore, parts that are easy to split and parts that are difficult to split exist in a mixed manner depending on the position, and sometimes the problem of being split during transportation and cleaning occurs.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 6399252
[0010] Patent Document 2: Japanese Patent Application Publication No. 2002-176119 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] In recent years, as the junction temperature of power semiconductor chips increases, ceramic circuit boards are required to have higher reliability. Therefore, there is a need for high-strength and thin ceramic circuit boards that have both heat dissipation and electrical insulation without sacrificing high reliability.
[0013] The embodiment solves such a problem and relates to a ceramic substrate having excellent cost performance and capable of efficiently manufacturing a small substrate from a large ceramic substrate having both heat dissipation and electrical insulation properties and having high strength and thinness.
[0014] Means for solving technical problems
[0015] A ceramic substrate of an embodiment has scribed lines, characterized in that a laser-processed surface including the scribed lines is formed by laser irradiation, and there are two or more peaks in the range of above 98 eV and below 106 eV in a spectrum obtained by measuring the laser irradiation area of the laser-processed surface using XPS (X-ray Photoelectron Spectroscopy). BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a top view showing an example of a ceramic substrate according to an embodiment.
[0017] Figure 2 This is a diagram schematically showing an example of the results of measuring the ceramic substrate according to the embodiment by XPS.
[0018] Figure 3 It is a schematic representation of the observation from above. Figure 1 A diagram showing an example of scribing lines on a substrate.
[0019] Figure 4 It is a plan view showing another example of the ceramic substrate according to the embodiment.
[0020] Figure 5 It is a plan view showing an example in which the ceramic substrate according to the embodiment has a circular shape.
[0021] Figure 6 It is a side view showing an example of the ceramic circuit board according to the embodiment.
[0022] Figure 7 It is a diagram showing an example of a laser processing method according to an embodiment.
[0023] Figure 8 It is a plan view showing another example of the ceramic substrate according to the embodiment.
[0024] Fig. 9 It is a plan view showing another example of the ceramic substrate according to the embodiment.
[0025] Fig.10 It is a plan view showing another example of the ceramic substrate according to the embodiment.
[0026] Fig.11 This is an enlarged side plan view showing another example of the ceramic substrate according to the embodiment.
[0027] Fig.12 It is a cross-sectional view showing an example of a portion cut along a scribe line in a divided ceramic substrate according to the embodiment.
[0028] Fig.13 It is a cross-sectional view showing an example of a portion cut along a scribe line in a divided ceramic substrate according to the embodiment.
[0029] Fig.14 This is a diagram showing an example of a method for producing a ceramic substrate according to an embodiment as a flow chart.
[0030] Fig.15 This is a diagram showing an example of a method for producing a ceramic substrate according to an embodiment as a flow chart.
[0031] Fig.16 This is a diagram showing an example of a method for producing a ceramic substrate according to an embodiment as a flow chart.
[0032] Fig.17 This is an enlarged plan view showing an example of positional deviation of the ceramic substrate according to the embodiment.
[0033] Fig.18 This is an enlarged plan view showing an example of a division failure of the ceramic substrate according to the embodiment.
[0034] Fig.19 It is a plan view showing another example of the ceramic substrate according to the embodiment. DETAILED DESCRIPTION
[0035] The scribed lines of the embodiment are set to represent the scribed lines before the ceramic laser scribed substrate is divided into ceramic split substrates and the scribed line marks after the ceramic split substrates are divided (hereinafter referred to as "scribed lines"). The ceramic substrate with scribed lines of the embodiment is characterized in that the scribed lines are formed by irradiation with a laser, and two or more peaks are observed in the range of 98 eV to 106 eV in the energy spectrum obtained by measuring using X-ray photoelectron spectroscopy (XPS). Two or more peaks in this range, for example, mean that three or four or more peaks can be observed. In addition, the "division" of the ceramic laser scribed substrate is also referred to as the "disconnection" of the ceramic laser scribed substrate.
[0036] Figure 1 , a top view of an example of a ceramic substrate of an embodiment is shown. Reference numeral 1 is a ceramic laser-scribed substrate, reference numeral 2 is a ceramic multi-piece processed substrate, reference numeral 3 is a scribed line for a non-through hole, reference numeral 4 is each ceramic split substrate that becomes a product, reference numeral 5 is a peripheral portion that is not used as a product, reference numeral 7 is a through hole, reference numeral 71 is a through hole as an example of the through hole 7, and reference numeral 72 is a cutout portion as an example of the through hole 7. The ceramic laser-scribed substrate 1 is generally composed of a ceramic multi-piece processed substrate 2 and a peripheral portion 5. In addition, in this specification, a ceramic substrate refers to a ceramic laser-scribed substrate 1, a ceramic multi-piece processed substrate 2, or a ceramic split substrate 4.
[0037] In addition, the laser processing in the present invention can be processed into any shape. The shape can be a scribed line 3 as described above, can be the formation of a cutout portion 72 suitable for threaded fixing, and can further be a hole processing. The cutout portion 7 is formed by overlapping a plurality of points based on a laser on a sintered substrate. In this way, by observing in which region more than two peaks are within the range of more than 98eV and less than 106eV, for example, in the case of a threaded fixing portion, it will lead to a reduction in uneven strength of the processed surface, which can increase the torque. In addition, when the scribed line is formed in the same manner, it will not be disconnected during transportation, and thus the occurrence of defects during segmentation can be suppressed.
[0038] exist Figure 1 , an example is shown in which a total of eight ceramic divided substrates 4 are processed by laser scribing, two in the vertical direction and four in the horizontal direction.
[0039] The ceramic laser scribing substrate 1 is not limited to such a shape. A ceramic split substrate 4 can be processed into a product shape by scribing lines 3, or multiple ceramic split substrates 4 with more than 2 vertical and 4 horizontal lines can be processed. In addition, it is not necessary to form scribing lines 3 on all 4 sides of the ceramic split substrate 4. Scribing lines 3 can be formed in one or more places. Figure 1In the top view, the ceramic dividing substrate 4 has a rectangular shape, but may have a roughly polygonal shape, may have a roughly circular shape, or may have a roughly polygonal shape with rounded corners. In addition, the scribed line 3 may also be provided on both the front and back sides of the ceramic laser scribed substrate 1. In addition, the scribed line 3 may be formed by combining the laser with other methods. In addition, in the laser processing of the invention, only one of the oscillation methods, continuous oscillation or pulse oscillation, may be used, or the two oscillation methods may be combined. In addition, the shape of the ceramic laser scribed substrate 1 may be as follows: Figure 5 In addition, the ceramic laser scribing substrate 1 can also be as follows Figure 4 The shape after being broken in this way has a shape like a cutout at the corner.
[0040] Ceramic substrates 1, 2 and ceramic circuit substrate 10 ( Figure 6 The portion of the ceramic divided substrate 4 shown in FIG. 1 is characterized in that two or more peaks are observed in the range of 98 eV to 106 eV in the spectrum obtained by XPS measurement.
[0041] When the ceramic substrates 1, 2, and 4 are silicon nitride substrates, the three-point bending strength can be set to a high strength of 600 MPa or more, and further to 700 MPa or more. In addition, there are materials with a thermal conductivity of 50 W / m·K or more, and further to 80 W / m·K or more. As materials with a thermal conductivity of 80 W / m·K or more, for example, materials of about 130 W / m·K can be cited. When the ceramic substrates 1, 2, and 4 are aluminum nitride substrates, the thermal conductivity can be set to a high thermal conductivity of 170 W / m·K or more, and further to 230 W / m·K or more. In addition, there are materials with a three-point bending strength of 350 MPa or more, and further to 450 MPa or more. In particular, in recent years, there are silicon nitride substrates and aluminum nitride substrates that have both high strength and high thermal conductivity.
[0042] The ceramic substrates 1, 2, and 4 may be single plates or may have a three-dimensional structure of a multilayer structure (a structure of a ceramic-conductor portion-ceramic-conductor portion). In addition, the ceramic substrates 1, 2, and 4 are preferably Si-containing ceramic substrates. Si-containing ceramics may include ceramics having one or more of SiAlon, silicon nitride, and silicon carbide as main components. As these Si-containing ceramics, a silicon nitride substrate is more preferably used.
[0043] The scribed line 3 is formed by laser processing. The laser used at this time is preferably selected from semiconductor laser, fiber laser, excimer laser, femtosecond laser, YAG laser, YVO laser, CO 2Any laser among laser, DDL laser, and blue laser. In addition, when using YAG laser, 2 times wave, 3 times wave, and 4 times wave can be used as needed. It is particularly preferred to use a laser with a wavelength of 1200nm. Thus, lasers with a wavelength of less than 1200nm include fiber lasers, excimer lasers, femtosecond lasers, YAG lasers, YVO lasers, and the like. Among these types of lasers, fiber lasers are further preferably used. When using such lasers, focusing lenses and reflectors can also be used as needed. In addition, when using a focusing lens, it is preferred to use its type and configuration under appropriate conditions according to the position and thickness of the substrate. By optimizing the conditions of the focusing lens in this way, the depth of focus can be adjusted. As described above, when forming the scribed line 3, it is preferred to move the substrate (for example, a sintered substrate after the sintering process) that serves as the basis of the ceramic laser scribing substrate 1 to form a groove shape. As a method of adjusting the laser to control the groove shape, two methods can be cited: a method of adjusting the direction by a reflector and a method of adjusting the laser itself, but in any case, it is possible that the position accuracy cannot be maintained according to the distance of the optical path, etc. In addition, the irradiation energy may vary depending on the length of the optical path, and since laser is a precision machine, if the laser itself is moved multiple times, the oscillation energy of the laser may vary over time. If such a problem occurs, it may be impossible to control the peak obtained by XPS.
[0044] Therefore, it is preferred to place the sintered substrate itself on a stage (stage) and move the stage itself. Alternatively, a method of moving the reflector when a reflector is used may be used, but if so, the longer the distance from the reflector to the object to be processed, the more likely the position accuracy will deteriorate. In addition, the fiber laser is based on the laser defined by JISZ 3001-5 (2013). The fiber laser may be a laser doped with Nd, Er, or Ho in a YAG crystal, or a laser using KLN, PPLN, sapphire, ruby, or the like. The fiber diameter is preferably less than 100 μm. In addition, the diameter accuracy is preferably an error of less than 0.001 mm, and preferably both parallelism and perpendicularity are controlled.
[0045] In addition, in the above-mentioned laser including the fiber laser, a crystal capable of wavelength conversion such as BBO (β-barium borate) can also be used as a 2-fold wave, 3-fold wave, 4-fold wave, etc. as needed. In addition, when using a fiber laser, the index type is more preferably any one of the step refractive index or the grating index. Here, the step refractive index refers to a uniform refractive index in the core, and on the other hand, the grating index is an index in which the refractive index in the core is uneven and the intensity distribution increases in the center. Therefore, at the same output, the grating index enables deeper processing. In addition, the oscillation mode can be single-mode or multi-mode, and single-mode is more preferably used. Here, the heat-affected zone (HAZ) is explained. The heat-affected zone extends in roughly concentric circles.
[0046] In addition, the formation of the scribed line can also use an auxiliary gas. The auxiliary gas used at this time is preferably nitrogen or air. The auxiliary gas is preferably ejected from the ejection port before the laser oscillates from the irradiation port of the laser. This is because, since the speed of light is very fast compared to the speed of sound, air resistance is generated when the auxiliary gas is ejected simultaneously with the oscillation, and it takes time for the auxiliary gas to reach the surface of the sintered substrate, resulting in a time difference. In such a case, the effect obtained by using the auxiliary gas may be reduced.
[0047] In addition, it is preferred that dust collection be performed regardless of the presence or absence of assist gas. By performing dust collection, high-temperature fine dust generated by laser irradiation can be removed. By performing dust collection in this way, the generation of bubbles that may be generated when the generated fine dust is deposited again can be prevented.
[0048] Figure 7 1 is a schematic diagram of the dust collection method in laser processing. Reference numeral 1 is a ceramic laser scribing substrate, reference numeral 11 is a metal circuit, reference numeral 14 is a laser processing machine, reference numeral 15 is particles generated by laser irradiation, and reference numeral 16 is a dust collector. Figure 7 As shown, when the laser processing machine 14 irradiates the laser to the ceramic laser-scribed substrate 1 on which the metal circuit 11 is formed, the dust collector 16 collects the particles 15. Thus, it is possible to suppress the phenomenon that the particles 15 cover the laser ejection port and destabilize the laser output, etc. By stabilizing the laser output in this way, it is also possible to suppress the time-dependent change of the laser product in the laser irradiation area.
[0049] In addition, the formation of the scribing line 3 can also be obtained by multiple laser irradiations. In the case of forming the scribing line 3 at the same location by multiple laser irradiations, it is preferred to separate the laser processing by an interval of more than 1 millisecond before the next laser processing. That is, in the case of laser irradiation of the same location, for example, the time interval between the nth (n: natural number) irradiation and the n+1th irradiation is more than 1μ second. In addition, the multiple time intervals that appear over time can be the same or different. For example, the interval between the nth irradiation and the n+1th irradiation can be different from or the same as the interval between the n+1th irradiation and the n+2th irradiation. This is because, in the case of multiple irradiations, by separating the time intervals, the next laser irradiation can be performed after the heat energy remaining on the sintered substrate due to the irradiation is reduced. The interval is further preferably less than 3 minutes. This is because, if the interval is longer than 3 minutes, the manufacturing takes time and the yield may deteriorate. In addition, the laser oscillation can be either a continuous wave (CW: Continuous Wave) or a pulse wave (PW: Pulse Wave), or a combination of a continuous wave and a pulse wave. When a pulse wave is used, a short pulse width of nanoseconds or less is more preferred. If the pulse width is long, the effect of laser irradiation becomes too large, oxidation proceeds, and thus two or more peaks may not be observed in the range of 98 eV to 106 eV.
[0050] Ceramic substrates 1, 2, 4 are preferably Si-containing ceramics, characterized in that a scribe line 3 is formed by laser processing, and two or more peaks are observed in the range of 98ev and below 106ev in the spectrum obtained by XPS measurement of the laser irradiation area as the laser processing side. In addition, the upper limit of the number of peaks is not particularly limited, preferably 10 or less, more preferably 5 or less, and further preferably 3 or less. When the peak intensity of the strongest peak above 98eV and below 101eV is set to I2, and the peak intensity of the strongest peak above 101ev and below 106eV is set to I3, the ratio of peak intensity, i.e., I3 / I2, is 0.4 or more and 12 or less. Furthermore, preferably I3 / I2 is 0.6 or more and 4.5 or less. More preferably, I3 / I2 is 0.9 or more and 4.1 or less. It is further preferred that I3 / I2 is 0.9 or more and 1.7 or less.
[0051] Here, the peak intensity is defined as the value obtained by subtracting the height of the baseline from the height of the peak at that time. Figure 2As shown, the baseline refers to a line connecting the end and the end of a peak with a straight line. The end of the peak is the position (minimum) where the slope of the spectrum becomes 0 for the first time when observed in one direction from the strongest part of the peak. However, in the case where the minimum exists between the maxima and the distance between the minimum and any one of the maxima is only less than 2 times the half-value width, it is preferred to use a minimum that exceeds other maxima. In addition, in the case where it is difficult to measure such a minimum, the height of one end is used as the height of the baseline. The I2 refers to the intensity of the peak of Si-Si, and I3 refers to the peak intensity of Si-. Therefore, adjusting the intensity ratio of the peak of Si-O to Si-Si to less than 2.5 refers to reducing the oxidation of Si caused by the thermal effect caused by laser processing.
[0052] In order to control the intensity of the peak in this way, it is preferred to perform laser processing on the sintered substrate while collecting dust in an environment with a humidity of 30% to 80% and below 28°C. More preferably, the humidity is 35% to 75%. If laser processing is performed in an environment with a humidity of less than 30%, static electricity is generated, and tiny bubbles may be easily generated due to the repulsion of charged particles from each other, so it is not preferred. On the other hand, when it is greater than 80%, water molecules in the atmosphere absorb the energy of the laser, and the silicon compound may hydrate. Therefore, if a hydrate is formed in this way, the absolute value of the Si-O peak may become smaller. This is because the non-shared electron pair of oxygen is not combined with Si, but is used to combine with hydrogen atoms. In addition, the molecules of the hydrate generated by absorbing the energy of the laser are hydrogen-bonded to each other. Hydrogen bonds are bonds with weaker bond energy than covalent bonds.
[0053] Therefore, if a large amount of hydrates are generated, the strength of the side surface may be reduced. Therefore, it is not preferred to generate a large amount of silicon hydrates. Here, humidity refers to the amount of water vapor in the atmosphere relative to the saturated water vapor amount, and the saturated water vapor amount increases as the temperature rises. Therefore, even if the humidity is the same, the higher the temperature, the more water molecules exist in the same volume. Therefore, if the temperature is high and exceeds 28°C, the saturated water vapor amount increases, and it may not be possible to fully obtain the effect of controlling the humidity below 80%. Therefore, the temperature during laser processing is preferably below 28°C.
[0054] In addition, the timing of irradiating the substrate that serves as the basis of the ceramic laser scribing substrate 1 with laser is not particularly limited, and is preferably after sintering. This is because, if it is a sintered substrate after sintering, the position of the scribing line with less size change in the subsequent process is easy to maintain. In addition, the conductor part can be joined after the scribing line is formed on the sintered substrate, or the scribing line can be formed after the conductor part is joined on the sintered substrate. Here, the conductor part can be joined after the etching process, before the etching process, or without the etching process. As a method without an etching process, a method of joining the conductor part that has been given a circuit shape in advance by punching and the like can be cited. In addition, the focusing distance is preferably greater than 0.5 mm, and preferably less than 30 mm. If the distance between the irradiation port and the substrate is less than 0.5 mm, the emitted plume adheres to the irradiation port, the energy of the laser processing, etc. tends to become unstable, and it may not be possible to fully maintain the position accuracy.
[0055] In addition, due to the instability of the output, the peaks observed in XPS may also change. On the other hand, if it is far beyond 30mm, the attachment of the plume can be suppressed, but the subtle angle difference formed by the laser and the ceramic substrates 1, 2, and 4 may have a greater impact on the position accuracy. In addition, as the focusing distance, the more preferred range is greater than 1mm and less than 15mm. If the molecular density is the same, the amount of water molecules present at each same distance is the same. Therefore, the farther the distance from the irradiation port, the greater the influence of water molecules on the output energy of the laser. In addition, the influence of humidity, temperature, etc. on the environment for laser processing may become too large. Therefore, the peaks observed with XPS may also change.
[0056] At this time, the XPS used Quantera_SXM manufactured by PHI. Therefore, it is preferable to use an XPS with performance equal to or better than this. The X-ray source used single crystal spectroscopic AlKα rays. The X-ray output at this time was 4.5 W. In addition, the diameter of the analysis area was 20 μm.
[0057] The absolute value (peak difference) of the value obtained by subtracting the value of the peak intensity of the strongest peak in the non-irradiated region from the value of the peak intensity of the strongest peak in the range of 528 eV to 536 eV in the irradiated region is preferably 2500 or less, and more preferably 1600 or less. More preferably, the peak difference is 1500 or less. It is further preferred that the peak difference is 800 or more and 1500 or less. In addition, the absolute value of the peak intensity of the strongest peak in the range of 528 eV to 536 eV in the irradiated region is preferably 1000 or more. This value of 1000 or more indicates that the energy density of the laser is high, indicating that the magnitude of the thermal effect on the non-irradiated region is suppressed. As described above, if the energy density is increased, the width of the scribed groove can be reduced, and the ratio of the area of the obtained ceramic split substrate 4 to the overall size of the ceramic laser scribed substrate 1 can also be increased. In addition, the absolute value of the peak intensity of the strongest peak in the range of 528 eV to 536 eV in the irradiated region is preferably 3500 or less. This is because if it is larger than 3500, the oxidation number of the Si component increases excessively, and there is a possibility that the value of I3 / I2 cannot be controlled.
[0058] In addition, it is preferred that the absolute value (peak difference) of the value obtained by subtracting the value of the peak intensity of the strongest peak in the range of 395 eV or more and 400 eV or less from the value of the peak intensity in the non-irradiated region in the irradiated region is 2500 or less. More preferably, the peak difference is 2200 or less. It is further preferred that the peak difference is 300 or more and 2000 or less. The peaks in this range are peaks derived from oxides.
[0059] A peak difference of 300 or more indirectly indicates that the thermal influence on the non-irradiated region is small and the influence of the laser light remains in the irradiated region.
[0060] Furthermore, it is preferred that the absolute value (peak difference) of the value obtained by subtracting the value in the non-irradiated region of the peak intensity of the strongest peak in the range of 282 eV to 288 eV from the value in the irradiated region of the peak intensity of the strongest peak in the range of 282 eV to 288 eV is 2500 or less. The peak difference is more preferably 1200 or less. The peak difference is more preferably 2500 or less. The non-irradiated region refers to a region with a portion at least 0.05 mm away from the laser processed surface as the center of the measurement portion.
[0061] This peak indicates the presence of carbon in 1S orbital. The presence of carbon in 1S orbital means that there is a bond with carbon, and the bond with the carbon is a single bond.
[0062] Therefore, a small peak difference in the intensities of these three peaks means that the change in their contents due to the presence or absence of laser irradiation is small.
[0063] Therefore, it is preferred that the peak difference of the three peak intensities is set to 2500 or less. In addition, the peak difference of the above two peak intensities is further preferably 2000 or less. In addition, the peak difference is preferably a certain degree. Therefore, the peak difference is more preferably 1000 or less. Here, the peak difference refers to the absolute value of the value obtained by subtracting the intensity of the peak in the range in the non-irradiation area of the laser from the intensity of the peak in the range in the irradiation area of the laser.
[0064] Peak difference C of peak intensity in the range of E [eV] or more and F [eV] or less E-F It is expressed by the following formula.
[0065] C E-F
[0066] =|(peak intensity in the range of E [eV] or more and F [eV] or less in the irradiated area)
[0067] -(Peak intensity in the range of E [eV] or more and F [eV] or less in the non-irradiated region)|
[0068] The peak difference can be indirectly obtained by comparing the obtained peak heights and obtaining the difference in peak height between the irradiated area and the non-irradiated area.
[0069] In addition, the ceramic to be scratched is more preferably composed of one or more of aluminum oxide, zirconium oxide, silicon nitride, sialon, and aluminum nitride as the main component. Here, the main component refers to a content of 50wt% or more. The ceramic to be scratched is more preferably a Si-containing ceramic. In addition, the type of ceramic is more preferably composed of silicon nitride, sialon, or silicon carbide as the main component. In addition, it is further preferred to use silicon nitride as the main component.
[0070] In addition, the ceramic substrates 1, 2, and 4 are preferably Si-containing ceramics. The Si-containing ceramics are more preferably silicon nitride or silicon carbide or sialon. The thickness of the ceramic substrates 1, 2, and 4 used at this time is not particularly limited, and is preferably 0.1 mm or more and 3.00 mm or less, and more preferably 0.2 mm or more and 2.5 mm or less. If the substrate is too thin to be less than 0.1 mm, it is easy to break during transportation after laser processing, which may have an adverse effect on transportation. On the other hand, if it is thicker than 3 mm, oxidation is excessively carried out during laser processing, and it may be impossible to observe more than two peaks on any laser processing surface.
[0071] When the ceramic substrates 1, 2, and 4 are Si-containing ceramics, according to the XPS spectrum, when the peak intensity of the strongest peak above 98 eV and below 101 eV is set to I2, and the peak intensity of the strongest peak above 101 eV and below 106 eV is set to I3, the peak intensity ratio, that is, I3 / I2, is preferably 2.5 or less. This I2 refers to the intensity of the Si-Si peak, and I3 refers to the peak intensity of Si-O. Therefore, adjusting the intensity ratio of the Si-O and Si-Si peaks to 2.5 or less means reducing the increase in the oxidation number of Si caused by the thermal effect caused by laser processing.
[0072] In addition, the peaks thus obtained are subjected to waveform separation and their integral values are compared. Here, the integral value represents the area of the peak. Therefore, the integral value depends on the peak intensity and the half-value width. The method of waveform separation refers to the spectrum of the non-irradiated area and the main peak in the range of more than 98 eV and less than 106 eV.
[0073] When the peak integral value of the strongest peak above 98 eV and below 101 eV is set as S2, and the peak integral value of the strongest peak above 101 eV and below 106 eV is set as S3, the peak intensity ratio, i.e., S3 / S2, is preferably 0.8 or more and 4.2 or less. By controlling the peak integral value in addition to the peak intensity, the generation ratio of the compound or simple substance that may form a Si-Si bond and the compound that may form a Si-O bond can be further controlled.
[0074] The depth of the laser-cut line 3 can be appropriately changed according to the application. For example, the laser processing depth D (in Figure 3 As a method for changing the laser processing depth D as described above, the laser processing depth D can also be changed by changing the moving (scanning) speed of the sintered substrate. The method of changing the scanning speed can be, for example, changing the speed at which the sintered substrate is moved. In addition, the scanning speed can be appropriately changed as needed, but if it is too slow, the heat effect may be too large due to the energy of the laser. Therefore, it is preferred to have a scanning speed above a certain level.
[0075] exist Figure 3On the laser processed surface of the ceramic laser scribing substrate 1 shown in the figure, the opening end 81 and the opening end 82 are respectively set as the ends of two locations on the opening (laser irradiation side) of the laser concave portion 8 and the perpendicular line of the laser scanning direction L. In contrast, it is preferred that the minimum angle (angle θ) of the deepest portion consisting of the deepest portion of the laser processing depth D located in the laser concave portion 8 and the two opening ends 81 and 82 is 3 degrees or more and less than 90 degrees. In addition, the angle θ is more preferably 5 degrees or more and 60 degrees or less. Furthermore, the angle θ is preferably 5 degrees or more and 45 degrees or less. As a further preferred range, the angle θ is 5 degrees or more and less than 30 degrees. As described above, by controlling the angle θ, when the ceramic laser scribing substrate 1 is divided along the scribe line 3 or when the cutout portion 72 is formed, the wasteful portion (ear) is reduced, and the position accuracy when disconnecting (dividing) or separating is improved. In addition, it is not limited to the improvement of the position accuracy when dividing, separating, etc. as described above. Even if there is a formation layer with different strengths during division, etc., and the angle θ becomes a sharp acute angle, it is possible not to be divided when it is not desired to be divided. In addition, on the laser processed surface of such a ceramic laser scribing substrate 1, in addition to the non-penetrating laser concave portion 8, and / or a partially penetrating laser concave portion (not shown) may be provided. That is, a through laser processing mark and a non-penetrating portion may coexist in one ceramic laser scribing substrate 1.
[0076] In addition, if Figure 8 to Figure 10 As shown, a ceramic laser-scribed substrate 1 having a ceramic multi-piece processing substrate 2 comprises: at least two scribed lines 31 extending outward from the intersection with other scribed lines 31 to the edge; scribed lines 32 between adjacent ceramic substrates 4; and other scribed lines 33 ( Figure 8 to Figure 10 Only the diagram in Figure 8 and Fig. 9 ). Moreover, it is preferred that the scribed line 32 extends outward from the intersection with the scribed lines 31 and 33. Figure 8 In the figure, two lines extending in the left and right directions of the paper are score lines 31. Fig. 9 In the figure, two lines extending in the vertical direction of the paper are score lines 31. Fig.10 In the figure, two extending in the horizontal direction of the paper and two extending in the vertical direction of the paper are four lines, namely, the scoring lines 31. As described above, if the scoring lines 32 are designed to protrude outward from the intersection with the scoring lines 31 and 33, the position of the scoring point (hereinafter referred to as "point") 3A may be shifted ( Fig.17 Example), the rupture failure U( Fig.18 On the other hand, Fig.11As shown, the ceramic laser-scribed substrate 1 has an extended width W2 of the scribed line 32 relative to the extended width W1 of the scribed line 31, and the width W2 is further preferably not less than 0.1 mm. In addition, it is preferred that the value (W2 / W1) of the above-mentioned extended width W2 relative to the extended width W1 is 1 / 2 or less. By making W2 / W1 less than 1 / 2 as described above, the ceramic laser-scribed substrate 1 will not be accidentally split (disconnected) during transportation, and the production cycle time can be shortened. It is more preferred that the above-mentioned W2 / W1 is less than 1 / 4. In addition,
[0077] In addition, as a process different from the laser processing for segmentation, the shape of the cutout of the screw fixing portion or the like may also be provided by laser processing. In addition, it is also possible to form only the cutout portion 72 without performing the laser processing for segmentation. Therefore, the shape of the laser processed surface of the ceramic substrates 1, 2, 4 is not particularly limited. In addition, the timing of segmentation or the like separation may be any timing. For example, such a separation process may be performed twice with other processes in between.
[0078] The scanning speed of the sintered substrate can be freely changed, but in order to observe more than two peaks within the range of 98eV or more and 106eV or less regardless of which range is measured, the variation of the scanning speed is preferably greater than 0 and less than 1500mm / s. On the other hand, in order to make the variation of the scanning speed of the sintered substrate completely 0, it is possible to spend costs. Therefore, by controlling the variation of the scanning speed on the sintered substrate to be as small as possible, it is also possible to exceed 0. This is to take into account the possibility that some time is required until the laser output is stabilized.
[0079] During laser processing of a sintered substrate, fine powders called plumes are sometimes generated. If the plumes are too close to the laser irradiation port, they may adhere to the laser irradiation port, destabilize the laser output, and clog the injection port.
[0080] In order to suppress the adhesion of these plumes, etc., dust collection is preferably performed. In addition, auxiliary gas may be used as needed. In addition, when performing the dust collection, it is preferred to use a dust collector, etc. In addition, the dust collector preferably has a filter, etc. Furthermore, in the case of using a dust collector having a filter structure as described above, it is preferred to remove fine powders, etc. attached to the above-mentioned filter portion as needed. By removing the fine powders attached to the filter portion in this way, the dust collection power can always be maintained to a certain extent. In addition, it also has the effect of suppressing the adhesion of fine powders, such as plumes that generate dust collection, to the substrate.
[0081] The attachments produced by laser processing of the sintered substrate are sometimes removed by subsequent steps, but may peel off if they remain on the surface of the ceramic laser-scribed substrate 1. In addition, if the laser output is increased without dust collection, the processing speed can be increased, but the damage to the laser processed surface becomes greater.
[0082] On the ceramic laser-scribed substrate 1 after laser processing of the sintered substrate, a conductor portion such as a metal plate can be joined to form a circuit portion (for example, Figure 6 In addition, the conductor part may be bonded to the sintered substrate to give the circuit shape, and then laser processing may be performed. In these cases, after the metal circuit 11 is formed on the ceramic laser scribing substrate 1, the ceramic circuit substrate 10 is divided (in Fig.14 as well as Fig.15 Alternatively, the ceramic laser scribed substrate 1 may be divided into the ceramic divided substrate 4, and then the metal circuit 11 may be formed to form the ceramic circuit substrate 10. Fig.14 and Fig.15 Other steps may or may not be included between step S2) shown and the dividing step (step S8) performed along the scribed lines after laser processing.
[0083] The metal used in the metal circuit 11 may be copper (Cu), copper alloy, aluminum (Al), etc. When copper is used as the metal circuit 11, oxygen-free copper may be used. In addition, the formation of the metal circuit 11 may be performed by etching, or a conductor portion having a circuit shape may be joined in advance. For example, a method of imparting the circuit shape in advance may be a method called punching.
[0084] like Figure 6 As shown, the ceramic split substrate (product part) 4 is preferably joined to the metal circuit 11 via a bonding layer (e.g., a brazing layer 13). In addition, when the metal heat sink 12 is joined to the ceramic split substrate 4, it is also preferably joined via a bonding layer (e.g., a brazing layer 13). In addition, as the brazing layer 13 between the ceramic split substrate 4 and the metal circuit 11, an active metal brazing material containing an active metal such as Ti (titanium) is preferably provided. In addition to Ti, active metals include Zr (zirconium), Nb (niobium), Hf (hafnium), etc. Therefore, other active metals may be used instead of Ti. The method of providing the bonding layer in this way may include a method of using a brazing paste and a method of using an alloy foil.
[0085] Therefore, if a bonding layer can be provided, the method can use foil or solder paste. As active metal solder, in addition to Ti, a mixture with Ag (silver) or Cu as the main component can also be cited. In addition, Ti preferably contains more than 0.1wt% and less than 10wt%, and Cu preferably contains more than 5wt% and less than 96wt%. In addition, as required, more than 1wt% and less than 35wt% of In (indium), Sn (tin), Al, Si (silicon), C (carbon), Mg (magnesium), Mo (molybdenum), Mn (manganese), W (tungsten), Re (rhenium), Os (osmium) can be added. Ag is the remainder. Therefore, Ag may not necessarily be contained. The active metal bonding method using active metal solder is to apply active metal solder paste on the surface of the ceramic split substrate 4, and a metal circuit 11 is arranged thereon. It is heated at 600°C or more and 900°C or less to bond. In addition, bonding can be performed using a method that requires vacuuming, or it can be performed under an inert atmosphere. Examples of the inert atmosphere include a nitrogen atmosphere (a molar fraction of 80% or more, more preferably a molar fraction of 85% or more), a rare gas atmosphere (an argon atmosphere, a neon atmosphere), and the like.
[0086] According to the active metal bonding method, the bonding strength between the ceramic divided substrate 4 and the metal circuit 11 can be set to 16 kN / m or more.
[0087] In addition, a metal thin film with one selected from Ni (nickel), Ag (silver), and Au (gold) as the main component may be provided on the surface of the metal circuit 11. Examples of these metal thin films include plated films and sputtered films. By providing a metal thin film, corrosion resistance and solder wettability can be improved. In addition, the coating may be provided locally or may cover the entire conductor portion. Furthermore, the ceramic circuit substrate 10 is not limited to Figure 6 The structure of the metal plate-ceramic substrate-metal plate described in the description may also be a 5-layer structure of metal plate-ceramic substrate-metal plate-ceramic substrate-metal plate. In addition, the metal plate described here may also be a metal plate with a circuit shape or a metal plate with a groove shape applied to the surface.
[0088] exist Figure 6 In the embodiment shown, the bonding area between the ceramic split substrate 4 and the metal heat sink 12 is different from the bonding area between the ceramic split substrate 4 and the metal circuit 11, but may be the same. In addition, the thicknesses of these metals may be the same or different. Furthermore, the metal heat sink 12 may be bonded to the ceramic split substrate 4 without the brazing layer 13. In addition, a conductor portion other than the brazing layer 13 may be provided between the metal heat sink 12 and the ceramic split substrate 4.
[0089] Such a ceramic circuit substrate 10 is suitable for a semiconductor module characterized in that a semiconductor element is mounted on a metal circuit 11 via a bonding layer.
[0090] In addition, electronic components such as semiconductor elements can also be mounted on the obtained ceramic circuit substrate 10. Furthermore, in addition to semiconductor elements, wire bonding and metal circuit 11 can also be bonded. The ceramic circuit substrate 10 after wire bonding can also be resin molded to form a semiconductor module. The semiconductor module of the embodiment is not limited to its structure. For example, wire bonding and lead frame can be either one. In addition, semiconductor elements, wire bonding and lead frames can also be provided in plurality on the metal circuit 11.
[0091] In addition, the bonding layer for bonding the semiconductor element and the lead frame can include solder, brazing material, etc. The solder is preferably lead-free solder. In addition, solder means a solder having a melting point of 450°C or less. Brazing material means a brazing material having a melting point of more than 450°C. In addition, a brazing material having a melting point of 500°C or more is called a high-temperature brazing material. High-temperature brazing materials include brazing materials with Ag as the main component. The brazing materials with Ag as the main component include Ag paste with controlled particle size, Cu paste with copper as the main component, etc.
[0092] When the ceramic circuit substrate 10 is sealed by resin molding, the laser scribed surface may be on the side opposite to the metal circuit 11 (the metal heat sink 12 side). This is because it is difficult for the resin to enter the recessed part generated by the laser scribed line, and there is a possibility of forming a void. Voids hinder heat dissipation, so it is preferable to form the scribed line on the heat sink side to suppress the generation of voids.
[0093] The miniaturization of semiconductor elements is progressing, while the heat generated from the chip is increasing. Therefore, in the ceramic circuit substrate 10 equipped with semiconductor elements, it is important to improve the heat dissipation. In addition, in order to improve the performance of the semiconductor device (semiconductor module), multiple semiconductor elements are mounted on the ceramic circuit substrate 10. Even if there is only one semiconductor element, if the intrinsic temperature of the element is exceeded, the resistance changes to a negative temperature coefficient on the negative side. Along with this, there is a phenomenon of thermal runaway and instantaneous destruction caused by concentrated flow of electric power. Therefore, it is effective to improve the heat dissipation. In addition, the semiconductor device of the embodiment can be used for PCU (Power Control Unit), IGBT (Insulated Gate Bipolar Transistor), IPM (Intelligent Power Module) modules of inverters such as automobiles (including electric vehicles), electric railway vehicles, industrial machinery, and air conditioners. With regard to automobiles, electric vehicles are progressing. Improving the reliability of semiconductor devices is directly related to the safety of automobiles. The same is true for railways, industrial equipment, etc.
[0094] Next, a laser scribing method for silicon nitride substrates in the ceramic substrates 1, 2, and 4 of the embodiments is described. The laser scribing method for silicon nitride substrates is not particularly limited as long as it has the above-mentioned structure, and the following method can be cited as a method for obtaining a good yield.
[0095] First, a silicon nitride substrate is prepared. In particular, considering the heat dissipation of the entire ceramic circuit substrate 10, it is preferred that the thermal conductivity is 50 W / m·K or more and the three-point bending strength is 600 MPa or more. Examples of materials having a thermal conductivity of 50 W / m·K or more and a three-point bending strength of 600 MPa or more include materials having a thermal conductivity of 130 W / m·K and a three-point bending strength of 750 MPa.
[0096] In addition, when the metal circuit 11 of the ceramic circuit substrate 10 is connected to the metal heat sink 12 through the through hole, a silicon nitride substrate having a through hole is prepared. In the case where the through hole is provided in the silicon nitride substrate, the through hole can also be provided in advance at the stage of the formed body. In addition, a process of providing a through hole (for example, a through hole) 71 in the silicon nitride sintered body can also be performed. The process of providing the through hole can include laser processing, cutting processing, etc., which are similar to laser scribing. Cutting processing can include hole opening processing using a drill bit, etc.
[0097] In addition, the scoring line 3 may not be Fig.13 The continuous groove 3B shown in the figure is formed by a combination of the point 3A and the shallow continuous groove 3B (omitted from the figure), or it can be formed by only Fig.12 Here, the dots 3A are formed by laser processing marks that are separated without overlapping, while the continuous groove 3B is formed by laser processing marks that at least partially overlap. When the scribed line 3 is formed by the dots 3A, the width W3 ( Fig.12 The average value of the width W3 is preferably 50 μm to 300 μm. It is further preferred that the average value of the width W3 is 50 μm to 150 μm. Furthermore, it is preferred that the width W4 of the scratch at point 3A (in Fig.12 The depth of point 3A is preferably 1 / 6 or more and 2 / 3 or less of the thickness of the substrate. In addition, the depth of point 3A is preferably 50 μm or more and 300 μm or less. It is further preferred that the depth of point 3A is 150 μm or more and 250 μm or less. In addition, in the laser processing, the scribing line is not limited to point 3A (at Fig.12 Figure 3B) or continuous groove 3B (in Fig.13 In addition to the above (shown in the figure), it is preferred to partially irradiate multiple times around the point 3A or the continuous groove 3B to form an auxiliary cutting line (auxiliary continuous groove or point). Figure 14 to Figure 16In step S2 shown, in addition to forming the dots 3A or the continuous grooves 3B, an auxiliary cutting line is formed to form the scribe line 3, which can further reduce the defect rate during the separation.
[0098] Preferably, before the step of setting the scribe line 3 on the ceramic substrate 1, 2, 4 (step S2), there is a step of placing the substrate on a table (stage) (step S2), and after the step of setting the scribe line 3 (step S2), there is a step of cleaning the surface by honing or sandblasting (step S2). Fig.16 As shown in FIG. 1 , after the process of dividing the peripheral portion (step S13), there may be a process of cleaning the surface (step S14). Fig.14 and Fig.15 As shown in FIG. 1 , after the step of joining the copper plates (step S5), the step of dividing into ceramic circuit substrates 10 (step S8) may be performed (step S8). Fig.14 Compared with the step of cleaning the ceramic circuit substrate 10 before the division (step S7) as shown in FIG. Fig.15 As shown in FIG. 1 , after the step of dividing the ceramic circuit substrate 10 (step S8), there is a step of cleaning the ceramic circuit substrate 10 (step S7). This is because tiny powders generated during the division may adhere to the ceramic circuit substrate 10, and the powders should be cleaned in step S7. Furthermore, the scribe line 3 may also be as follows: Fig.19 That is used to separate only the scribed lines of the peripheral portion.
[0099] The silicon nitride substrate is placed on a precision processing table of a laser processing machine such as a fiber laser (step S1). The silicon nitride substrate is irradiated with laser light to form laser processing marks such as a scribing line 3 composed of dots 3A ( Fig.12 At this time, according to the laser processing machine 14 ( Figure 7 The conditions shown in FIG. 2 are used to form a point 3A of a specified size. In addition, the laser processing is preferably performed by moving the precision processing table. This is because, during laser processing, if the processing is controlled by moving the laser or changing the direction of the reflector, it may be difficult to adjust the scanning speed.
[0100] A metal plate (metal circuit 11 and metal heat sink 12) is bonded to a silicon nitride substrate, that is, a ceramic laser-scribed substrate 1, on which scribe lines 3 are formed.
[0101] The bonding of the silicon nitride substrate and the metal plate is preferably carried out by an active metal bonding method. The active metal bonding method uses an active metal brazing material mixed with an active metal such as Ti. In addition, a mixture of Ti and Cu can be cited as an active metal brazing material. In addition, the active metal brazing material may also contain Ag as needed. When containing Ag, it is preferably 99.5wt% or less. In addition, it is more preferably 95wt% or less. By controlling the Ag content in this way, the effect of not being easy to cause ion migration can be expected. It is known that ion migration is more likely to occur with Ag than with Cu. On the other hand, if there is more silver, the reliability of bonding at high temperatures is improved. Therefore, it is more preferred to freely adjust the amount of silver within a range of more than 0wt% and less than 95wt% according to needs or uses. For example, Ti is more than 0.1wt% and less than 10wt%, Cu is more than 0.5wt% and less than 60wt%, and Ag is the remainder.
[0102] Therefore, it is not necessary to contain Ag, and it may contain about 95wt%. In addition, as needed, one or more selected from In, Sn, Al, Si, C, Mg, Mo (molybdenum), Mn (manganese), W (tungsten), Re (rhenium), Os (osmium) may be added in a total of more than 1wt% and less than 35wt%. The active metal brazing filler metal is paste-formed. The paste is formed by mixing the brazing filler metal components with organic matter, but the brazing filler metal components need to be mixed evenly. This is because if the brazing filler metal components are unevenly distributed, the brazing will be unstable and become the cause of poor joining.
[0103] The active metal solder paste is applied to the ceramic laser-scribed substrate 1. A copper plate is placed thereon. Next, a step of heating the substrate at a temperature of 600°C to 900°C is performed to bond the substrate. The heating step is performed in a vacuum or a non-oxidizing atmosphere as required. In the case of performing the heating step in a vacuum, the temperature is preferably 1×10 -2 Pa or less. Examples of the non-oxidizing atmosphere include nitrogen atmosphere, argon atmosphere, helium atmosphere, neon atmosphere, etc. Here, the non-oxidizing atmosphere is not particularly limited, but refers to an atmosphere in which the oxygen partial pressure is 10% or less.
[0104] By setting the atmosphere in a vacuum or a non-oxidizing atmosphere, it is possible to suppress oxidation of the bonding layer, thereby improving the bonding strength.
[0105] The conductor part to be joined may be a conductor part that has been pre-processed into a pattern shape for circuit formation, or a single plate that has not been processed into a pattern shape. In addition, when a single plate is used, etching is performed after joining to process it into a pattern shape. In this case, the metal circuit 11 may also be formed on the surface opposite to the surface where the scribed lines are formed. Through this process, a silicon nitride metal circuit substrate as a ceramic circuit substrate 10 can be manufactured.
[0106] Next, a process of bonding semiconductor elements and the like to the silicon nitride metal circuit substrate is performed. A bonding layer is provided at the location where the semiconductor element is bonded. The bonding layer may be solder or brazing material, or may be a silver layer using silver paste or the like. Alternatively, it may be a copper layer using copper paste. A bonding layer is provided, and semiconductor elements are provided thereon. Furthermore, as required, a lead frame is bonded via the bonding layer. Furthermore, wire bonding is provided as required. Furthermore, the required number of semiconductor elements, lead frames, and wire bonding is provided. The semiconductor element, lead frame, and silicon nitride circuit substrate to which wire bonding is performed are molded with resin, thereby sealing the interior.
[0107] The laser scribing method of the silicon carbide substrate in the ceramic substrates 1, 2, and 4 of the embodiment is described. First, a silicon carbide substrate is prepared. In particular, if the heat dissipation of the ceramic circuit substrate 10 as a whole is considered, it is preferred that the thermal conductivity is 150 W / m·K or more and the three-point bending strength is 400 MPa or more. As long as the laser scribing line of the silicon carbide substrate has the above-mentioned structure, the manufacturing method thereof is not particularly limited, and as a method for obtaining a good yield, the same manufacturing process as the above-mentioned silicon nitride substrate and silicon nitride circuit substrate is adopted.
[0108] (Examples 1 to 22, Comparative Examples 1 to 7)
[0109] For the ceramic substrates 1, 2, and 4, silicon nitride substrates (thermal conductivity: 90 W / m·K, three-point bending strength: 650 MPa) having a size of 200 mm in length and 180 mm in width and a thickness of 0.32 mm and 0.50 mm were prepared.
[0110] In addition, a silicon carbide substrate (thermal conductivity: 300 W / m·K, three-point bending strength: 400 MPa) having a size of 200 mm in length and 180 mm in width and a thickness of 0.635 mm and 0.80 mm was prepared.
[0111] Next, for Figure 1 A substrate (e.g., a sintered substrate) which is the basis of a ceramic laser-scribed substrate as shown in the figure was subjected to dust collection on one side surface, and 8 laser processes were performed on each of 200 substrates under the conditions of Examples 1 to 22 and Comparative Examples 1 to 7. The processed shapes are shown in Table 2. In addition, the scribed lines and dots of Examples 2 to 4, 10 to 12, 18, and 21 shown in Table 2 correspond to those of Comparative Examples 1 and 4. In addition, the case where both the temperature and humidity conditions are met is recorded as "0 (circle)" in the "Temperature·Humidity" column of Table 1, and the case where either the temperature or humidity is not met is recorded as "× (cross)".
[0112] In addition, the case where "0 (circle)" is recorded in the "Laser Condition" column of Table 1 indicates that the pulse width is set to a nanosecond level or less and dust collection is performed. The case where the "focusing distance" satisfies the condition is recorded as "0 (circle)" in the "focusing distance" column. In addition, in the laser processing in the comparative example, no auxiliary gas is used.
[0113] In addition, the ceramic substrate processed by laser under each condition is transferred under the same condition and then subjected to the following steps (referred to as post-steps). The following steps are honing, cleaning, drying, and transfer.
[0114] When such a process is performed, the substrates that are cut (divided) partially or along the scribe line or offset from the cutting line are shown in Table 2 as the division ratio.
[0115] In addition, the angle θ formed by the deepest part of the groove and two locations (both ends) of the opening end was determined. The angle θ is recorded in the column "Laser Processing Angle" in Table 2.
[0116] The measurement results of the examples and comparative examples are shown in Tables 1 and 2. (In Table 1, silicon nitride (Si 3 N 4 ) substrate is “SiN” and silicon carbide substrate is “SiC”.
[0117] [Table 1]
[0118]
[0119]
[0120] [Table 2]
[0121]
[0122]
[0123] In the ceramic substrates 1, 2, and 4 of Examples 1 to 17, the conditions in the laser processing are within the range of the preferred embodiment. On the other hand, the ceramic substrates of Comparative Examples 1 to 7 are outside the range of the preferred embodiment. Figure 1 The cutout portion is shown as 72 in the figure.
[0124] Next, the laser processing surface in the split part was measured by XPS under various conditions. Tables 3 and 4 show the measurement results. The device used in the measurement was Quantera SXM manufactured by PHI. In addition, the X-ray source was single crystal spectroscopic AlKα ray. The X-ray output was 4.5W, the analysis area was φ20μm, the geometry was 45 degrees, and the pass energy was -69.00eV (0.125 / Step)
[0125] [Table 3]
[0126]
[0127]
[0128] [Table 4]
[0129]
[0130]
[0131] As can be seen from Tables 3 and 4, in all of the ceramic substrates 1, 2, and 4 of Examples 1 to 22, the number of peaks at 98 eV or more and 106 eV or less measured by XPS is within a preferred range.
[0132] When comparing the Examples and Comparative Examples using Tables 1 to 4, the Comparative Examples had a high rate of breaking in the subsequent process of 4% or more regardless of the laser processing angle. On the other hand, in the Examples where the preferred peaks were observed by XPS, the breakage rate was small, less than 4%.
[0133] It can be seen that the laser processed surface is strengthened and unnecessary division (fracture) does not occur by observing two or more peaks in the range of 98 eV to 106 eV. The above two or more peaks are observed on any laser processed surface.
[0134] In addition, in the examples, no defects (fractures, cuts, cracks) of disconnected portions were observed. On the other hand, these defects were observed in some cases in the comparative examples.
[0135] These defects are considered to be caused by the instability of output during laser processing (caused by adhesion of plume to the irradiation port, etc.).
[0136] Therefore, it is understood that it is important to optimize various conditions in laser processing and control the obtained XPS spectrum.
[0137] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are included in the invention described in the claims and the scope of their equivalents. In addition, the above-mentioned embodiments can be implemented in combination with each other.
[0138] Description of Reference Numerals
[0139] 1…ceramic substrate (e.g., ceramic laser-scribed substrate);
[0140] 2…ceramic substrates (e.g. ceramic multi-piece processing substrates);
[0141] 3…marking lines;
[0142] 4…ceramic substrate (e.g. ceramic split substrate (product part));
[0143] 5…Peripheral parts (non-product parts);
[0144] 6…Laser processed surface;
[0145] 7…through hole;
[0146] 71 ... through hole (e.g., through hole);
[0147] 72 ... through hole (e.g., cutout);
[0148] 8…Laser recess;
[0149] 9…non-laser irradiated surface (non-laser processed surface);
[0150] 10…ceramic circuit substrate;
[0151] 11…Metal circuit;
[0152] 12…Metal heat sink;
[0153] 13… solder layer;
[0154] 14…Laser processing machine;
[0155] 15…particles generated by laser irradiation;
[0156] 16…Dust collector;
[0157] W1…exposed width of the peripheral part;
[0158] W2…Exposed width of the scribed line.
Claims
1. A ceramic substrate, characterized in that: In a spectrum obtained by measuring a laser irradiated region of a laser processed surface by XPS (X-ray photoelectron spectroscopy), two or more peaks exist in a range of 98 eV to 106 eV.
2. The ceramic substrate according to claim 1, characterized in that: If the peak intensity of the strongest peak above 98 eV and below 101 eV in the spectrum obtained by measuring the laser irradiation area by the XPS is set to I2, and the peak intensity of the strongest peak above 101 eV and below 106 eV is set to I3, then the peak intensity ratio, i.e., I3 / I2, is greater than 0.4 and less than 12.
3. The ceramic substrate according to claim 1, characterized in that: If the peak intensity of the strongest peak above 98 eV and below 101 eV in the spectrum obtained by measuring the laser irradiation area by the XPS is set to I2, and the peak intensity of the strongest peak above 101 eV and below 106 eV is set to I3, then the peak intensity ratio, i.e., I3 / I2, is greater than 0.6 and less than 4.
5.
4. The ceramic substrate according to any one of claims 1 to 3, characterized in that: The absolute value of the value obtained by subtracting the peak intensity of the strongest peak in the range of 528 eV to 536 eV in the spectrum obtained by measuring the laser irradiation area and the laser non-irradiation area using the XPS is less than 1600.
5. The ceramic substrate according to any one of claims 1 to 4, characterized in that: The absolute value of the value obtained by subtracting the peak intensity of the strongest peak in the range of 395 eV to 400 eV in the spectrum obtained by measuring the laser irradiation area and the laser non-irradiation area using the XPS is less than 2500.
6. The ceramic substrate according to any one of claims 1 to 5, characterized in that: The absolute value of the value obtained by subtracting the peak intensity of the strongest peak in the range of 282 eV to 288 eV in the spectrum obtained by measuring the laser irradiation area and the laser non-irradiation area using the XPS is less than 2500.
7. The ceramic substrate according to any one of claims 1 to 6, characterized in that: The ceramic substrate is a Si-containing ceramic.
8. A ceramic circuit substrate, characterized in that: The ceramic substrate according to claim 1 has a circuit portion formed on the surface thereof.
9. The ceramic circuit substrate according to claim 8, characterized in that: A metal circuit as the circuit portion is formed on one or more of the surface irradiated with the laser light and the surface opposite to the surface irradiated with the laser light.
10. The ceramic circuit substrate according to claim 8, characterized in that: The circuit portion contains at least one selected from aluminum, aluminum alloy, copper, and copper alloy.
11. The ceramic circuit substrate according to claim 10, characterized in that: Molding is performed using resin.
12. A semiconductor device, characterized in that: The ceramic circuit board according to claim 8 is provided with a semiconductor element mounted thereon.
13. A method for manufacturing a ceramic substrate, characterized in that: After forming dots or continuous grooves on a portion of at least one side of a sintered substrate by fiber laser, auxiliary dots or continuous grooves are further formed by the fiber laser one or more times to form scribed lines, thereby manufacturing the ceramic substrate according to claim 1.
14. The method for manufacturing a ceramic substrate according to claim 1, characterized in that: When the sintered substrate is irradiated with laser light, the humidity is set to 30% to 80% and the temperature is set to 28° C. or less, thereby producing the ceramic substrate according to claim 1 .
15. A method for manufacturing a ceramic divided substrate, characterized in that: A ceramic laser-scribed substrate as the ceramic substrate according to claim 1 is manufactured by forming a scribed line on at least one side of a sintered substrate using a fiber laser, and a stress is applied to the ceramic laser-scribed substrate to divide the ceramic laser-scribed substrate, thereby manufacturing a ceramic divided substrate as the ceramic substrate.
